Attitudes towards Israel in Tunisian political debate: from Bourguiba to the new constitution. Issue 3 (26th May 2016) - Petrucci, Filippo; Fois, Marisa
ABSTRACT: Tunisia has developed an original diplomatic approach to the Israeli–Palestinian conflict. Relations between Tunisia and Israel (and more generally between Israel and the Arab world) have also influenced internal relations within Tunisia and the reactions and decisions of its Jewish community. This paper describes the evolution of the Tunisian government's attitudes towards Israel and the Palestinian issue in the post-independence era until the approval of the new Tunisian Constitution in 2014. The debate over whether to include an article regarding 'the criminalisation of normalisation with Israel' in the recently approved Constitution was considerable. Issues related to Israel have thus gained prominence in national debate, following a period in which they were primarily discussed by Ben Ali's political opponents. Through an analysis of articles, books, Internet sources and presidential speeches, this article examines the different positions taken by Tunisia towards Israel and how they have evolved over time.